Analysis of Behavior and Factors Affecting Cost stickiness On Manufacturing Company Listed on the Indonesia Stock Exchange Period 2014-2018 - Siti Nuridah; Rimi gusliana; Lies Zulfiati (BPJP - STEI, 2019)
Abstract—This study aims to determine the stickiness of cost behavior and the factors that affect the cost stickiness on manufacturing companies listed in Indonesia Stock Exchange. The behavior of sticky cost in this study visits of sales, general and administration costs are categorized into several industry groups to see the degree of sticky cost of each industry group per year, in addition to the factors that affect the cost stickiness among others, is a capital intensity ratio, employee intensity ratio , and management incentives as measured by free cash flow as well as the addition of the control variable is size. The method used is multiple linear regression analysis using the equation as measured by Anderson, Banker and Janakiraman. The sample is determined by purposive sampling method with the number of samples are 97 companies during the period 2014-2018. The results in this study are all manufacturing companies in Indonesia are sticky cost behavior. Sticky degrees largest and smallest cost occurs in animal feed and other sectors it is proved that the company's management in the sector are not consistent in supervising and controlling sales, general and administrative costs. Then about the factors that affect the cost stickiness are the results that: 1) Capital intensity ratio does not influence the degree of stickiness cost, 2) Employee intensity ratio affects the degree of cost stickiness, 3) Free cash flow does not affect the degree of cost stickiness